Studi Prototipe Pengaruh Sudut Kemiringan Poros Baling-Baling Terhadap Daya Dorong Kapal Laut - Munawir, Ahmad; Rubiono, Gatut; Mujianto, Haris (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2017)
Banyuwangi has 18.738 fishermen that use wood boats with diesel engine. This research is aimed to get the effect of shaft angle inclination due to boat speed. The research is done by prototype experiment. A small scale boat with 25 cm length, 7,75 wide and 2 meter motion water field. The shaft angle inclination is vary as 0o, 5o, 10o,15 o, 20o, 25o dan 30o. The number of blade propeller is vary as 2 and 4 blades. Motion time is measured by a stopwatch. The data are analyzed to get boat speed. The result shows that the shaft angle inclination has effect due to boat speed. The angle of 15o has the best performance with 2 blades propeller.